Analog & RF circuits: design & implementation - Zainol Murad, Sohiful Anuar (Universiti Malaysia Perlis, 2019)
This book entitled ANALOG AND RF CIRCUITS Design and Implementation intentionally covers both analog and radio frequency circuits design and optimization approaches, which is the key feature that distinguishes it from other existing books. It focuses on theoretical aspects of various designs as well as simulation and measurement for analog and RF integrated circuits and systems. The book also highlights the unique design issues, which facilitates the reader to be able to understand more advanced researches at a good pace. Furthermore, each chapter and subject’s area is beginning with basic principles and fundamentals and goes into further details with selected design examples with in-depth discussions and up to date references. Read this book to learn more about the design techniques for realizing analog and RF circuits. This book is a comprehensive reference and well-founded material for students as well as electronics engineers and researchers in academia and industry working in the areas of circuits and systems design.